Effect of TiO2 Doping on the Structure and Microwave Dielectric Properties of Cordierite Ceramics. Issue 6 (20th March 2015) - Wu, Song; Song, Kaixin; Liu, Peng; Lin, Huixing; Zhang, Fangfang; Zheng, Peng; Qin, Huibin; Alford, N.
<x xml:space="preserve">Abstract</x> The (1−x)Mg2Al4Si5O18–xTiO2 |(1−x)MAS‐xT| (0 ≤ x ≤ 0.35) cordierite ceramics are fabricated by solid‐state reaction method for obtaining near‐zero temperature coefficient of resonant frequency (τf). The XRD and SEM results show that (1−x)MAS‐xT (0 ≤ x ≤ 0.10) ceramics exhibit single cordierite solid solution, whereas as 0.15 ≤ x ≤ 0.35, present composite phases of Mg2Al4Si5O18 solution and TiO2. Rietveld refinements of XRD data suggest that the [(Si4Al2)O18] hexagonal shape in cordierite structure happens to alternate change from nonsymmetrical hexagonal rings to almost centrosymmetrical equilateral rings as x increases to 0.10 comparing to that of x = 0. As Ti4+ ions squeeze into the [(Si4Al2)O18] rings structure, the orientation and shapes of the rings begin to rotate and expand from initial state of [1–20] (x = 0) to near [210] direction (x = 0.10), and then continue to expand toward close to [110] direction (x = 0.25). Due to centrosymmetry adjustment of [(Si4Al2)O18] hexagonal rings and of other microstructure factors improvement, the (1−x)MAS‐xT (x = 0.10) cordierite solution achieves optimum quality factor Qf: εr = 6.3, Qf = 55 400 GHz (17.6 GHz), τf = −21 ppm/°C. The (1−x)MAS‐xT (x = 0.25) composites obtain a near‐zero temperature coefficient of resonance frequency: εr = 6.8, Qf = 37 800 GHz (18.4 GHz), τf = −0.2 ppm/°C.